EMS: a model for a world monetary order? - Peter Bofinger; Christina Gerberding (Intereconomics, 1988)
In the debate about the world monetary order there is agreement that greater stability in international currency relationships would be desirable. Could a system of fixed exchange rates between the currencies of the major industrial countries put an end to the present instability? What would be the advantages and weaknesses of such a system modelled on the EMS?
Keywords: 330; Exchange Rate Policy